2017
DOI: 10.18203/2319-2003.ijbcp20170820
|View full text |Cite
|
Sign up to set email alerts
|

Variation of hemodynamic response following induction and tracheal intubation: etomidate vs midazolam

Abstract: Background: Induction and endotracheal intubation are invariably associated with certain cardiovascular changes during anaesthesia practice and can lead to sudden swings of blood pressure, arrhythmias, MI and cardiovascular collapse especially in geriatric and haemodynamically unstable patients. Therefore it is desirable to use a safer agent with fewer adverse effects to minimise these complications. Present prospective randomized study is designed to compare the haemodynamic alterations and various adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…We found that after induction, there was a decrease in heart rate from the baseline in both the groups which on comparison was found to be non-significant (p value 0.0615). The findings of this study corroborates with the study report of Sarkar Molly et al (2005), 9 Shagun Bhatia Shah et al (2015), 13 Kaushal Ram Prasad et al (2015), 14 Binod Pegu et al (2017) 15 that decrease in heart rate is more on induction with injection propofol than with injection etomidate which on comparison found to be non-significant. The mean MAP is significantly decreased in both the groups (p<0.001) but the fall is more in group A and at 5 min after intubation MAP is increased in both the groups which becomes comparable in both the groups at 10 min.…”
Section: Discussionsupporting
confidence: 90%
“…We found that after induction, there was a decrease in heart rate from the baseline in both the groups which on comparison was found to be non-significant (p value 0.0615). The findings of this study corroborates with the study report of Sarkar Molly et al (2005), 9 Shagun Bhatia Shah et al (2015), 13 Kaushal Ram Prasad et al (2015), 14 Binod Pegu et al (2017) 15 that decrease in heart rate is more on induction with injection propofol than with injection etomidate which on comparison found to be non-significant. The mean MAP is significantly decreased in both the groups (p<0.001) but the fall is more in group A and at 5 min after intubation MAP is increased in both the groups which becomes comparable in both the groups at 10 min.…”
Section: Discussionsupporting
confidence: 90%